Peripheral blood CD3+ T‐cell gene expression biomarkers correlate with clinical frailty in patients with haematological malignancies. (29th June 2022) - Fell, Geoffrey; Rosko, Ashley E.; Abel, Gregory A.; Dumontier, Clark; Higby, Kelly J.; Murillo, Anays; Neuberg, Donna S.; Burd, Christin E.; Lane, Andrew A.
Summary: Older patients with cancer often receive treatment regimens based on their age without considering other objective factors that may influence outcomes. Assessment of frailty can identify older patients who are robust and therefore more likely to benefit from intensive treatment, or conversely, frail and might instead be offered alternative approaches. However, such assessment requires specialised training and dedicated clinical resources. Alternative quantitative biomarkers associated with frailty are lacking. Here, we asked if expression signatures of 74 immune cell, ageing, and senescence‐related messenger RNAs in purified peripheral blood T cells could identify associations with clinical frailty in patients with haematological malignancies. We studied 69 patients between the ages of 36 and 92 years (median 76 years) with leukaemia, lymphoma, or multiple myeloma, across two institutions. Expression of four genes (aryl hydrocarbon receptor [ AHR ], CD27, CD28, and interleukin‐2 receptor subunit alpha [ IL2RA ; CD25]) in T cells was associated with frailty, independent of age. An expression‐based regression model had 76% sensitivity and 90% specificity to assign a patient as robust. These data identify measurable peripheral blood correlates of clinical frailty and suggest biomarkers for future prospective assessment.